Efforts to Improve Learning Outcomes Elementary School Science Thematic Through Implementation of the Project Based Learning ( PjBL ) Learning Model (Journal Intellectual Sufism Research (JISR), 2023)
Research purposes This is increase results Study elementary science thematic through application of learning models Project Based Learning ( PjBL ) . Research methods is study action class with using II cycle . Study implemented at Madrasah Ibtidaiyah Negeri (MIN) 1 Surabaya City for students class V. Data collection techniques using observation , questionnaires , and tests . Research data obtained _ analyzed use technique Miles and Huberman's data analysis includes data collection , data reduction , data presentation , and withdrawal conclusion / verification . Research result showing that a) Activity Study student during application of the PjBL model experience enhancement from katgorei Enough become very OK , b) Test results evaluation Study student experience enhancement after application of the PjBL model , with percentage completeness by 61% in cycle I increased to 88% in cycle II, and 3) Response student to application of learning models PjBL showing response positive . With so , in fact whole can concluded that explanation of learning models Project Based Learning ( PjBL ) can increase results Study elementary school science thematic
Keywords: Learning outcomes; science thematic; Project Base Learning; PjBL